Case Report: Chronic Active Epstein–Barr Virus Infection With Subcutaneous Nodules and Systemic Damage - Luo, Huating; Yuan, Zhe; Qin, Bo (Frontiers in Medicine, 2022)
Chronic active Epstein–Barr virus (CAEBV) infection is a rare and progressive systemic lymphoproliferative disorder often beginning as an infectious mononucleosis (IM)-like illness. It manifests with fever, splenomegaly, hepatitis, lymphadenopathy, and occasionally cytopenias, pneumonitis, and vasculitis. We report a 23-year-old woman with fever and subcutaneous nodules first appearing on the limbs and then spreading to the body. Peripheral blood EBV antibodies were elevated and EBV-DNA loads significantly increased. A skin and lymph node biopsy identified T cell-based lymphocyte infiltration and EBV-encoded RNA positivity (EBER+). CAEBV was finally diagnosed. During the illness, her disease progressed to hemophagocytic syndrome (HPS). The patient then successfully received an allogeneic hematopoietic stem cell transplantation (HSCT) at 6 months. Current follow-up at 2 years indicated a stable condition and six negative EBV-DNA tests, and we reviewed the clinical manifestations, mechanism, diagnosis and differential diagnosis, treatment, and prognosis of CAEBV. Finally, subcutaneous nodules may occur when CAEBV invades the skin; therefore, clinicians must identify the cause of these nodules early. HSCT is effective but its timing must be appropriate.